The impact of the adoption of IFRS on turnover: a comparative analysis with the Moroccan accounting framework - LAOUANE, Adil; TORRA, Mohamed (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The development of financial markets, the importance of the transparency of financial information disclosed, and the consequences of globalization have led to changes in accounting science, particularly in its financial reporting dimension. In the case of Morocco, the Moroccan accounting framework remained frozen in the face of changes induced by IFRS standards. The process of convergence of accounting standards with international standards (IFRS) has so far been limited to financial sector groups and listed companies. Our article discusses the impact of the introduction of IFRS on the way of calculating turnover.We will seek to show, on the basis of a comparative analysis, how the change in accounting standards could affect the net income of Moroccan adoptive companies.